2016
DOI: 10.1016/j.ijsu.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Human immune-cell response towards diverse xenogeneic and allogeneic decellularized biomaterials

Abstract: Even decellularized or cross-linked xenogenic cardiovascular and reconstructive biomaterials elicit increased human immune responses not seen in the majority of allogenic specimens tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The decellularized tissue may expose new protein, and the decellularization protocol may also have a significant impact on the response of human mononuclear cells [59]. Rieder et al [60] reported that decellularized vascular wall elicited more immune cell proliferation than native equivalent, and hence, it proved the above hypothesis. It also hypothesized that opsonization would be the way of inflammation response and can occur through preformed antibody or binding of unspecific plasma protein to the surface.…”
Section: Immunogenicity Against Decmmentioning
confidence: 90%
“…The decellularized tissue may expose new protein, and the decellularization protocol may also have a significant impact on the response of human mononuclear cells [59]. Rieder et al [60] reported that decellularized vascular wall elicited more immune cell proliferation than native equivalent, and hence, it proved the above hypothesis. It also hypothesized that opsonization would be the way of inflammation response and can occur through preformed antibody or binding of unspecific plasma protein to the surface.…”
Section: Immunogenicity Against Decmmentioning
confidence: 90%
“…Animal-free matrices are very useful for 3D bioprinting of grafts [ 35 ] and decellularized matrices are ideal materials for generating a bioink [ 35 ]. As animal-derived matrices have to deal with xenogenic and ethical issues [ 36 ], plant-derived matrices are a worthy option. Matrices obtainable via plant tissue decellularization [ 37 ] are extremely challenging in the tissue engineering field and scaffolding for 3D cell cultures, however, they could need smart functionalization because of some lack of biochemical mammalian cues [ 38 ].…”
Section: Biomaterials: Overview Of Natural Polymersmentioning
confidence: 99%
“…So far, the only clinical application of xenotransplantation in the field of cardiac repair is the endoventricular injection of a decellularized extracellular porcine myocardial matrix. The outcomes of this trial (NCT02305602) will reveal if this strategy is worth a further pursuit considering that decellularized porcine pulmonary arteries were previously shown to induce a strong immune cell response in vitro 47 .…”
Section: Cell Therapy Of Ischemic Heart Diseasementioning
confidence: 99%